Monotonic and Fracture Behaviours of Bolted Connections with Distinct Bolt Preloads and Surface Treatments - Vítor M.G. Gomes; Mariana Rodrigues; José A.F.O. Correia; Miguel A.V. Figueiredo; Abílio M.P. de Jesus; António A. Fernandes (Fracture and Structural Integrity)
This paper presents a research about the monotonic and failure behaviours of bolted joints made of thin plates of S350GD and S355MC steels grades, which are used for rack structures. A full factorial test matrix was performed considering two joints configurations (1+1 and 4+4 double shear bolted joints), two material thicknesses (2 and 3mm), three coatings (“black steel”, zinc coating, zinc plus paint) and two preload levels (25%×70%Fu and 70%Fu). Tests were performed under static monotonic loading until failure. Slip tests were also performed according to the EN 1090-2 standard to evaluate joint slip factors for the three material surface conditions. In addition to the experimental tests, numerical simulation of static tests were performed using elastoplastic material behaviour, based on Mises yield theory and isotropic hardening identified with experimental tensile testing data. The models were able to reproduce conveniently the ultimate loads of the joints and failure modes, including clamping and friction effects.